The Effect Of The Effect of Training, Teaching Experience and Work Motivation on The Performance of State Vocational School Teachers Jeneponto - Rezky, Rezky; Muhammad Idkhan, Andi; Rahmah, Nur (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to analyze the influence of training, teaching experience, and work motivation on the performance of State Vocational High School teachers in Jeneponto Regency, both partially and simultaneously. Method: The study used Explanatory Research with a quantitative approach through a cross-sectional survey design. The study population came from three State Vocational High Schools in Jeneponto Regency totaling 134 teachers, with a sample of 100 teachers obtained using the Proportionate Random Sampling technique. Data were collected using a structured questionnaire and analyzed using simple and multiple linear regression. Results: The results showed that training, teaching experience, and work motivation had a positive and significant effect on teacher performance (Sig. <0.05). Simultaneously, the three variables explained 67.4% of the variation in teacher performance (R² = 0.674), while 32.6% was influenced by other factors outside the model. Novelty: This study emphasizes the importance of an integrated approach in improving the performance of vocational teachers by integrating aspects of competence, professional experience, and work motivation in the context of regional Vocational High Schools. These findings provide an empirical basis for formulating more contextual and sustainable vocational school teacher development policies at the local level.